2015
DOI: 10.1093/femsle/fnv102
|View full text |Cite
|
Sign up to set email alerts
|

The effect of prolonged storage on the virulence of isolates ofBacillus anthracisobtained from environmental and animal sources in the Kars Region of Turkey

Abstract: The stability of the plasmid-mediated virulence factors of Bacillus anthracis, a tripartite toxin located on pXO1 and an antiphagocytic capsule encoded by genes located on pXO2, following long-term storage was investigated. A collection of 159 isolates of B. anthracis were collected from the Kars region of Turkey between 2000 and 2013 and stored at -20°C in Brucella broth supplemented with 20% glycerine. A total of 142 isolates were recovered of which one failed to express a capsule upon primary culture. A fur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0
3

Year Published

2016
2016
2018
2018

Publication Types

Select...
5

Relationship

5
0

Authors

Journals

citations
Cited by 7 publications
(10 citation statements)
references
References 26 publications
0
7
0
3
Order By: Relevance
“…However, there is limited information on the retention of the virulence plasmids under environmental conditions , as most studies have focused on laboratory storage (Turnbull et al 1992;Bowen and Quinn 1999;Marston et al 2005;Buyuk et al 2015). When compared to these reports, our data suggests a lower frequency of pXO2 loss (1.75% compared to ~20%) suggesting that long term storage has a detrimental effect on plasmid stability (Marston et al 2005;Buyuk et al 2015). While the underlying mechanisms responsible for the loss of pXO2 during long term laboratory storage have yet to be determined the results highlight the importance of using fresh isolates to determine plasmid stability in the field.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…However, there is limited information on the retention of the virulence plasmids under environmental conditions , as most studies have focused on laboratory storage (Turnbull et al 1992;Bowen and Quinn 1999;Marston et al 2005;Buyuk et al 2015). When compared to these reports, our data suggests a lower frequency of pXO2 loss (1.75% compared to ~20%) suggesting that long term storage has a detrimental effect on plasmid stability (Marston et al 2005;Buyuk et al 2015). While the underlying mechanisms responsible for the loss of pXO2 during long term laboratory storage have yet to be determined the results highlight the importance of using fresh isolates to determine plasmid stability in the field.…”
Section: Resultsmentioning
confidence: 99%
“…Colonies were also screened for capsule expression (encoded by pXO2) by culture on 0.7% bicarbonate agar supplemented with 10% horse serum in the presence of carbon dioxide. Suspect colonies were also analysed by PCR for the presence of the virulence plasmids pXO1 and pXO2 as described by Buyuk et al (2015) and Wang et al (2011). While a single gene target (PA) was used to confirm the presence of pXO1, multiple gene targets spanning the entire circumference of the pXO2 plasmid were employed (Wang et al 2011).…”
Section: Methodsmentioning
confidence: 99%
“…In this outbreak, individuals involved in the slaughtering process did not use personal protective equipment as the authors suggested in agricultural rural areas; animal owners and shepherds should be aware of and educated in the use of personal protective equipment such as gowns, gloves, and goggles when in contact with sick animals or transporting infected carcasses [2,10,13] as this could reduce the risk of human infection. A vaccination program was also initiated against anthrax for livestock using the Sterne vaccine (34F2).…”
Section: Discussionmentioning
confidence: 99%
“…The presence of the B. anthracis virulence plasmids, pXO1 and pXO2 were assessed using PCR as described by Buyuk et al [10] In brief, a 25 μl reaction mixture containing 12.5 μl Taq PCR Master Mix (Qiagen, UK), 2.5 μl primer mix (Cap6/103 or PA5/8), 2.5 μl template DNA, and 7.5 μl dH 2 O (supplied as part of the Taq PCR Master (<7 km from Karakimse) in June 2013; however, no movement of animals between Duver and Karakimse could be confirmed.…”
Section: Pcr Analysis Of Virulence Plasmidsmentioning
confidence: 99%
“…Soil was collected from two sites which had yield B. anthracis spores on previous occasions ( Buyuk et al, 2015 ). Fifty gram samples from the top 2 cm of the soil were removed using a metal trowel from each of five randomly selected sectors of a 2 by 2 m grid constructed with metal pegs and string which had been overlaid over the center of the contaminated site.…”
Section: Methodsmentioning
confidence: 99%